Efeitos da caprinocultura sobre a diversidade taxonômica em comunidades vegetais na caatinga - Nunes, João Paulo de Andrade (Universidade Federal Rural do Semi-Árido, 2019)
The impact of goat farming, deforestation and historical use of the areas on the taxonomic diversity of Caatinga is still poorly understood. This work aimed to evaluate the effects of anthropogenic activities on the taxonomic diversity in Caatinga, measuring the influence of disturbances such as goat grazing, deforestation and the history of use of these areas, in order to obtain useful information for management and the conservation of remaining resources. The study was conducted in 15 farms located in the municipalities of Pedro Avelino, Angicos and Lajes, in the Central Mesoregion of Rio Grande do Norte, where interviews were conducted with the owners, addressing questions regarding the history of use areas, mainly to agropastoral practices. From them, the animal loads of the areas were calculated and classified as deforestation in old and recent. In these, the tree and herbaceous community were surveyed using the quadrant and needle methods. Then, Shannon and Simpson richness indices for each area were calculated. Multiple linear regression and quadratic regression models were applied to verify the influence of animal load, grazing years and deforestation on the mentioned diversity indexes. To compare possible differences in the composition of the tree-shrub and herbaceous strata between areas, the species were grouped hierarchically by cluster analysis from the dissimilarity matrix by the Bray-Curtis distance. A total of 6300 individuals were found in the tree stratum, distributed in 10 families and 23 species. The Fabaceae, Euphorbiaceae and Apocynaceae families were the most abundant. For the herbaceous stratum a total of 24 families and 69 species were found. The families Poaceae, Malvaceae, Fabaceae and Convolvulaceae presented the highest richness. Shannon diversity indices ranged from 1.247 ± 0.301 and Simpson's diversity from 0.368 ± 0.122 for the tree-shrub strata and 0.816 ± 0.566 and 0.348 ± 0.246 for herbaceous. The Shannon and Simpson index of the communities is not influenced by the variables animal load, grazing years, but is influenced by deforestation. Cluster analysis showed the presence of three distinct groups between the study areas in the tree-shrub stratum. The results indicated a very low species richness independent of grazing intensity and deforestation. The influence on diversity between areas subject to deforestation at different times, associated with the maintenance of low richness and dominance of pioneer species, such as the jurema preta, suggest a "stagnation" in the succession of the plant community in the studied region. The diversity did not differ along the grazing gradient, which is probably related to the relatively low animal load values of the study areas, to the extent that grazing does not lead to reduction of tree plant diversity. Goat grazing does not influence the species diversity of the plant communities studied. Low herbaceous richness may be related to species selection by goats and sheep and the history of use of the study areas. The observed practices led to a stagnation of the succession of the vegetation structure of the studied sites. It is concluded that goat breeding, of fundamental importance for the region, should continue to occur with management practices appropriate to the functioning of the ecosystem.
Keywords: Caatinga; Caprinocultura; Desmatamento; Diversidade Alfa; Distúrbio Antrópico Crônico; Alpha diversity; Caatinga; Caprinoculture; Chronic Anthropic Disturb; Deforestation; CIENCIAS BIOLOGICAS::ECOLOGIA